(untitled) (Jurnal Bina Praja, 2021)
The impact of the Covid-19 pandemic, which has had a major impact on people’s lives, has prompted the president and his cabinet members to respond with various policy stimuli. This study wants to see the solidity of the president’s assistants in responding to President Jokowi’s general policies in dealing with the Covid-19 pandemic and analyze the causes of the ineffectiveness of policies taken with an applied communication approach the policy field. By using the literature study method, this research finds that the implementation of policies made by the president’s assistants is not in line with the wishes of the president as the Head of Government. This is probably due to the political power dynamics contained in the Jokowi’s second term coalition members. In addition, the interests of coalition members may impact the process and decision-making of a policy. The results of this study recommend that the government strengthen the role of the structure in charge of managing and ensuring that the policies taken by the president’s assistants in handling Covid-19 are in line with the president’s wishes. Furthermore, it is necessary to communicate the policy to all stakeholders involved in the policy process so that the policies taken in handling Covid-19 do not represent the political interests of coalition members. In addition, to maintain the solidity of the coalition cabinet in handling Covid-19, the positions of cabinet members involved in the policy implementation process must submit to the power of the President as Head of